THE BLANKON: UNIQUE BEVERAGE WITH DISTINCTIVE AROMA FROM KAWISTA - Khinsa Naura Nisrinathira; Lokita Rizky Megawati; M. Syamsul Ma’arif (School of Business, IPB University (SB-IPB), 2020)
Kawista is a fruit that belongs to oranges, it has round shape with thick and hard skin and special aroma. The purpose of this research is to identify customer needs for non-coffee beverage and produce The Blankon. The method used was customer development that is focused on customer discovery by using canvas model. The study conducted in coffee shops in Bogor City from February to March 2020. The results showed that The Blankon answered the customers’ wants. The sweet levels classified as adequate (not too sweet) and not leaving traces of sweetness in the mouth. The Blankon has distinctive aroma, and refreshing as drinks. Based on the result, about 92% of respondents were potential to choose The Blankon as their beverages. Keywords: build the product, business model canvas, customer discovery, kawista